Investigating factors affecting social presence and user satisfaction with mobile instant messaging - Ogara, Solomon O.; Koh, Chang E.; Prybutok, Victor R. (Elsevier Ltd., 2014)
The purpose of this study is to examine the factors that influence social presence and user satisfaction with Mobile Instant Messaging (mIM). The proposed research model integrates channel expansion, social influence, social presence and media richness theories, to explain how user experience, social influence, and medium richness influence social presence and user satisfaction with mIM. A total of 239 students from a state university in the US participated in this study. Data was collected via a web-based survey. The results suggest that user experience, social influence, and perceived richness are important drivers for social presence and user satisfaction in mIM. The implications of the study findings are discussed in the paper.
http://dx.doi.org/10.1016/j.chb.2014.03.064
Keywords: User satisfaction; User experience; Social presence; Social influence; Richness; Mobile Instant Messaging